Design and implementation of AIS instruments using big data and AI approaches - Lingam, G; Pavan Kumar, A (International Journal of Engineering and Technology, 2018)
This paper present the theoretical aspect of inventing a new device which is called as an Artificial intelligence system (AIS) is a Automatic medical device is a self-detection diseases machine to identify the trace element & recognizing the diseases and advising the patients to be aware of their health. A trace element is an element (e.g., lead, selenium, arsenic) that is present in a human body and it is very small, making it a challenge to measure them accurately. This research focus is on trace elements that are in the human body and the proposed to devise (now in theoretical aspect) a new medical device to identify all the trace elements in the human body and recognizing the diseases and checking the health of the people because they are essential for proper growth. All essential elements are for human nutrition. . It can be helpful to cure many diseases in future at home itself. The death ratio can also be reduced and human can live longer. The people can check their daily nutrition using this one.Â Â Â